The Measurement on Service Quality of E-commerce Live Streaming: Modeling and Its Validity - Zhao, Weihong; Qi, Yu (Transactions on Economics, Business and Management Research, 2024)
This study investigates the conceptual model and measurement scale of the service quality of E-commerce Live Streaming (ELS). Findings indicate that the service quality of ELS comprises interaction quality (entertainment and professionalism), environmental quality (activeness and convenience), and outcome quality (promotion and dependability). The relative predictability of these dimensions on the service quality of ELS also falls into a particular order: Interaction quality is most predicable, followed by outcome quality, then environmental quality. Finally, each of the dimensions has positive effects on consumers’ purchase intention by effecting their cognitive trust and emotional trust. And interaction quality is most predicable for effecting consumers’ cognitive trust. Environmental quality is most predicable for effecting consumers’ emotional trust. These results altogether provide valuable insights into the service quality management of ELS.